Does storage conditions of whole blood or blood cells effect genotoxicity assessment by comet assay?. (June 2021) - Baydaş, Zeynep; Bacanli, Merve; Başaran, Nurşen
Abstract: Comet assay, applied to in vitro, in vivo and ex vivo systems, is a quick, simple, and sensitive method for the detection of genotoxicity. In general, fresh whole blood or peripheral blood mononuclear cells (PBMCs) are used in the assay for the determination of DNA damage and repair. In this study, the effects of storage conditions on genotoxicity assessed by Comet assay in human whole blood and lymphocyte samples, were evaluated. Whole blood and lymphocyte samples were stored at 4 °C for 1, 2, 3, 4, 5 and 7 days; at −20 °C for 1 month and at −80 °C for 3, 6 and 12 months. 1% DMSO was used as cryoprotectant. No significant differences in DNA damage were demonstrated in all of the storage conditions and durations, and the results were similar according to the median values (p < 0.05). According to Spearman or Pearson correlations, an important correlation was found between the DNA damage of the fresh samples and the samples which were kept at −80 °C for 6 months with temperature and time (p < 0.01 for Pearson and p < 0.05 for Spearman). The results of this study indicated that blood and lymphocyte samples stored in +4 °C, −20 °C and −80 °C up to 12 months can be used instead of fresh samples especially in human biomonitoring studies. Highlights: The comet assay is one of the most popular assays for the assessment of DNA damage. Whole blood and lymphocytes are particularly useful for human biomonitoring studies. However, it is often not possible to work on the same day when the blood is collected. It is necessary to store the samples and examine at different times. The results indicated samples stored in +4 °C, −20 °C and −80 °C can be used in the assessment of DNA damage.